Girard and Heidegger: Mimesis, Mitsein, Addiction - Duyndam, Joachim (The European legacy, 2015)
In his essay "Peter’s Denial," René Girard draws a parallel between mimesis and Martin Heidegger’s concept of being-with (Mitsein). In this essay I explore this parallel through a third, intermediate term—addiction—on the assumption that living in a world governed by mimesis, according to Girard, and living in the modus of Mitsein, according to Heidegger, can both be characterized as a kind of addiction. The clarification of the parallel between mimesis and Mitsein through this intermediate term may contribute to a better understanding of a central concept of Heidegger’s philosophy and, at the same time, bring into view the philosophical dimension of Girard’s mimetic theory. In my conclusion I propose Levinas’s ethical approach as a possible cure to the addiction to mimesis and being-with.